Trends of regenerative tissue engineering for oral and maxillofacial reconstruction in veterinary medicine - Purbantoro, Steven Dwi; Taephatthanasagon, Teeanutree; Purwaningrum, Medania; Hirankanokchot, Thanyathorn; Peralta, Santiago; Fiani, Nadine; Sawangmake, Chenphop; Rattanapuchpong, Sirirat (Frontiers in Veterinary Science, 2024)
Oral and maxillofacial (OMF) defects are not limited to humans and are often encountered in other species. Reconstructing significant tissue defects requires an excellent strategy for efficient and cost-effective treatment. In this regard, tissue engineering comprising stem cells, scaffolds, and signaling molecules is emerging as an innovative approach to treating OMF defects in veterinary patients. This review presents a comprehensive overview of OMF defects and tissue engineering principles to establish proper treatment and achieve both hard and soft tissue regeneration in veterinary practice. Moreover, bench-to-bedside future opportunities and challenges of tissue engineering usage are also addressed in this literature review.